Purification and biophysical characterisation of HIV-1 Vpu and identification of novel drug molecules - Njengele, Zikhona (My University, 2019)
HIV-1 has developed various strategies to evade host immune responses, and these are mainly carried out by viral accessory proteins. HIV-1 Vpu, which is encoded by HIV-1 and some SIV isolates, plays many crucial roles in the pathogenesis of HIV-1. These include cell surface reduction of CD4; enhancement of virion release from infected cells by antagonising the host restriction factor, BST-2, as well as cell surface down-modulation of the major histocompatibility complex class I (MHC I) and NKT-and-B antigen (NTB-A) ligands recognised by cytotoxic T lymphocytes (CTL) and Natural Killer (NK) cells, respectively. By interfering with the expression of these molecules, HIV-1 Vpu helps HIV-1 infected cells evade recognition by these immune cells. The roles played by HIV-1 Vpu in ensuring that HIV-1 evades immunity make this protein an attractive target for new therapeutic interventions against the HIV-1 infection. In this study, a library of 24 novel small molecular compounds was screened against the interaction of HIV-1 Vpu with BST-2. From the screening assays, two compounds, Compound 1 (ethyl 2-[(5-phenyl)-1H-imidazol-1-yl]acetate) and Compound 8 (5-(3methoxyphenyl)-1H-imidazol-1-yl]acetohydrazide), were identified as potential hits with inhibition percentages of ~80% and 69%, and IC50 values of 11.6 ± 1.1 µM and 17.6 ± 0.9 µM, respectively. The compounds were further characterised through a range of direct and cell-based assays in vitro to determine their cytotoxicity, antiviral activity and potential ability to directly bind HIV-1 Vpu. The identified compounds were tested alongside 6-aza-2thiouridine and Lapachol, two compounds that previously showed activity in restoring cell surface expression levels of BST-2 in the presence of HIV-1 Vpu. Compound 1 and Lapachol were able to inhibit the replication of HIV-1 (EC50 = 6.3 ± 0.7 and 17.3 ± 0.6 µM, respectively) at non-toxic concentrations (CC50 = 184.5 ± 0.8 and 152.8 ± 0.6 µM) in vitro. While Compound 8 did not show any traits of toxicity towards the mammalian cells used in our experiments (CC50 = 159.5 ± 0.9 µM), this compound did not exhibit any appreciable activity in hindering the replication of HIV-1 in the in vitro phenotypic assay. Conversely, 6aza-2-thiouridine was toxic towards MT-4 cells (CC50 = 14.6 ± 0.5 µM), and as a result, the antiviral activity of this compound could not be correctly confirmed. The binding energetics of the compounds to HIV-1 Vpu were determined using ITC. 6-aza-2-thiouridine exhibited highest affinity for HIV-1 Vpu (KD of 4.5 µM), followed by Compound 1 (18.5 µM) and lastly, Compound 8 (20.8 µM). The binding of these compounds to HIV-1 Vpu proved to be enthalpically driven, with ΔH values of -3.98, -0.99 and -23.36 kJ/mol for Compound 1, Compound 8 and 6-aza-2-thiouridine, respectively. The results proved that these compounds do interact directly with HIV-1 Vpu, albeit with low binding affinity. The binding energetics for Lapachol, however, could not be evaluated, as this compound frequently precipitated out of solution at the molar ratios required for ITC experiments. Overall, Compound 1 showed greater activity in inhibiting the HIV-1 Vpu/BST-2 interaction, was more potent in hindering the replication of HIV-1 in vitro and also showed better affinity for HIV-1 Vpu compared to Compound 8; and as a result, this compound was identified as a better lead compound. To the best of our knowledge, this is the first study to provide a detailed assessment of the binding energetics that occur between HIV-1 Vpu and potential inhibitors. The chemical structure of the active compound identified in this study can provide basis for development of novel HIV-1 inhibitors that target the binding HIV-1 Vpu to BST-2. Through structural modifications, the biological activity of this compound can be improved
A Thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2019